1989
DOI: 10.1152/ajpgi.1989.257.2.g202
|View full text |Cite
|
Sign up to set email alerts
|

Receptor occupation, calcium mobilization, and amylase release in pancreatic acini: effect of CCK-JMV-180

Abstract: We examined the relationships between receptor occupation, calcium mobilization, and stimulated amylase release for cholecystokinin octapeptide (CCK-8) and for CCK-JMV-180, an analogue of the COOH-terminal heptapeptide of CCK having the structure Boc-Tyr(SO3)-Nle-Gly-Trp-Nle-Asp-2-phenylethyl ester using dispersed acini from rat pancreas. CCK-8 and CCK-JMV-180 each bind to two classes of CCK receptors: one class has a high affinity for CCK-8 and CCK-JMV-180 and the other class has a low affinity for CCK-8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
60
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 0 publications
5
60
1
Order By: Relevance
“…CCK-JMV antagonized the ability of CCK-8 to stimulate tyrosine phosphorylation of all six phosphospecific sites. This result confirmed that activation of the low affinity CCK A receptor state, for which CCK-JMV is an antagonist (31,33), is also involved in the ability of CCK to cause maximal stimulation of tyrosine phosphorylation at each site in each kinase. With the use of CCK-JMV, we could demonstrate that in the case of the PYK2 phosphospecific sites, ϳ45% of the phosphorylation was mediated by the high affinity state, whereas in the case of the three FAK phosphospecific sites, less than 20% of the phosphorylation was mediated by the high affinity state.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…CCK-JMV antagonized the ability of CCK-8 to stimulate tyrosine phosphorylation of all six phosphospecific sites. This result confirmed that activation of the low affinity CCK A receptor state, for which CCK-JMV is an antagonist (31,33), is also involved in the ability of CCK to cause maximal stimulation of tyrosine phosphorylation at each site in each kinase. With the use of CCK-JMV, we could demonstrate that in the case of the PYK2 phosphospecific sites, ϳ45% of the phosphorylation was mediated by the high affinity state, whereas in the case of the three FAK phosphospecific sites, less than 20% of the phosphorylation was mediated by the high affinity state.…”
Section: Resultssupporting
confidence: 75%
“…Our results support the conclusion that CCK is stimulating tyrosine phosphorylation at each of the three FAK-and PYK2-specific sites by activation of both receptor states; however, the extent of participation by each state varies with the different specific phosphorylation site. This conclusion is supported by the finding that CCK-JMV, which functions as an agonist at the high affinity receptor state and as an antagonist on the low affinity receptor state in rat pancreatic acini (31)(32)(33), stimulated tyrosine phosphorylation at each of the three sites in each kinase, demonstrating that stimulation of the CCK A receptor high affinity state participates in phosphorylation at each of three sites in both kinases. However, CCK-JMV did not stimulate to the same maximal extent as CCK, suggesting that activation of the high affinity state of the CCK A receptor only accounted for some of the stimulation caused by CCK.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations